A Call for Incorporating Social Research in the Global Struggle against Snakebite - Gutiérrez, José María (2015)
In Africa, Asia, Latin America, and parts of Oceania, envenoming after snakebite is a serious public health problem. Conservative data suggest that between 1.2 and 5.5 million people suffer snakebites every year, resulting in 25,000 to 125,000 deaths and leaving approximately 400,000 victims with permanent sequelae. Despite its significant impact on human health, this disease remains largely neglected by national and international health authorities, funding agencies, pharmaceutical companies, patients’ organizations, and health advocacy groups